2015
DOI: 10.1016/j.cyto.2015.01.009
|View full text |Cite
|
Sign up to set email alerts
|

Seeking balance: Potentiation and inhibition of multiple sclerosis autoimmune responses by IL-6 and IL-10

Abstract: The cytokines IL-6 and IL-10 are produced by cells of the adaptive and innate arms of the immune system and they appear to play key roles in genetically diverse autoimmune diseases such as relapsing remitting multiple sclerosis (MS), rheumatoid arthritis (RA) and systemic lupus erythematosus (SLE). Whereas previous intense investigations focused on the generation of autoantibodies and their contribution to immune-mediated pathogenesis in these diseases more recent attention has focused on the roles of cytokine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
51
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(53 citation statements)
references
References 174 publications
1
51
1
Order By: Relevance
“…Significant enrichment of the core node Haemophilus was observed in infants with PBB, and it was negatively correlated with other microbial colonizers, including Lactococcus, Bacillus and Clostridium. Previous reports have shown that Bacillus affect the secretion of IL-17 indirectly (27), and Clostridium could promote T regulatory (Treg) cell differentiation, which were crucial for inflammation reactions (22,28). In infants with PBB, the relative abundances of aforementioned genera decreased as Haemophilus increased, and this was found to aggravate microbial imbalance and expand the immune response in the respiratory mucosa.…”
Section: Discussionmentioning
confidence: 92%
“…Significant enrichment of the core node Haemophilus was observed in infants with PBB, and it was negatively correlated with other microbial colonizers, including Lactococcus, Bacillus and Clostridium. Previous reports have shown that Bacillus affect the secretion of IL-17 indirectly (27), and Clostridium could promote T regulatory (Treg) cell differentiation, which were crucial for inflammation reactions (22,28). In infants with PBB, the relative abundances of aforementioned genera decreased as Haemophilus increased, and this was found to aggravate microbial imbalance and expand the immune response in the respiratory mucosa.…”
Section: Discussionmentioning
confidence: 92%
“…B cells were noted to secrete primarily IL-6 and IL-10 in granulomas from control animals and global reductions of these cytokines within the granulomas of rituximab-treated macaques could be attributed to B cell depletion. Indeed, B cells are prodigious producers of IL-6 in other immune settings, such as multiple sclerosis (48). IL-6 has multiple roles in inflammation, particularly B cell expansion (34,48) and T cell development (49).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, B cells are prodigious producers of IL-6 in other immune settings, such as multiple sclerosis (48). IL-6 has multiple roles in inflammation, particularly B cell expansion (34,48) and T cell development (49). A decrease in IL-6 suggests that the inflammatory response within the B cell-depleted granuloma may be less robust compared to control granulomas since IL-6 is involved in coordinating immune cell recruitment, particularly neutrophils and T cells during the acute phase of infection (50,51).…”
Section: Discussionmentioning
confidence: 99%
“…NO generated by inducible nitric oxides synthase endows macrophages with cytostatic or cytotoxic activity against bacteria, viruses and tumor cells 25 . The cytokines IL-6 is produced by cells of adaptive and innate arms of the immune system and appears to play a key role in genetically diverse autoimmune diseases and respond to pathogens 26 . There is mounting evidence that the cytokines are related to Tolllike receptors TLRs down-stream NF-κB pathway, which suggested M1 macrophage are activated 27,28 .…”
Section: Discussionmentioning
confidence: 99%